Beneficial Effects of Halogenated Anesthetics in Cardiomyocytes: The Role of Mitochondria - José Luis Guerrero-Orriach; María Dolores Carmona-Luque; Aida Raigón-Ponferrada (MDPI AG, 2023)
In the last few years, the use of anesthetic drugs has been related to effects other than those initially related to their fundamental effect, hypnosis. Halogenated anesthetics, mainly sevoflurane, have been used as a therapeutic tool in patients undergoing cardiac surgery, thanks to the beneficial effect of the cardiac protection they generate. This effect has been described in several research studies. The mechanism by which they produce this effect has been associated with the effects generated by anesthetic preconditioning and postconditioning. The mechanisms by which these effects are induced are directly related to the modulation of oxidative stress and the cellular damage generated by the ischemia/reperfusion procedure through the overexpression of different enzymes, most of them included in the Reperfusion Injury Salvage Kinase (RISK) and the Survivor Activating Factor Enhancement (SAFE) pathways. Mitochondria is the final target of the different routes of pre- and post-anesthetic conditioning, and it is preserved from the damage generated in moments of lack of oxygen and after the recovery of the normal oxygen concentration. The final consequence of this effect has been related to better cardiac function in this type of patient, with less myocardial damage, less need for inotropic drugs to achieve normal myocardial function, and a shorter hospital stay in intensive care units. The mechanisms through which mitochondrial homeostasis is maintained and its relationship with the clinical effect are the basis of our review. From a translational perspective, we provide information regarding mitochondrial physiology and physiopathology in cardiac failure and the role of halogenated anesthetics in modulating oxidative stress and inducing myocardial conditioning.